Cross-presenting CD103(+) dendritic cells are protected from influenza virus infection - Helft, Julie (American Society for Clinical Investigation, 2012)

(untitled)
CD8(+) cytotoxic T cells are critical for viral clearance from the lungs upon influenza virus infection. The contribution of antigen cross-presentation by DCs to the induction of anti-viral cytotoxic T cells remains controversial. Here, we used a recombinant influenza virus expressing a nonstructural 1–GFP (NS1-GFP) reporter gene to visualize the route of antigen presentation by lung DCs upon viral infection in mice. We found that lung CD103(+) DCs were the only subset of cells that carried intact GFP protein to the draining LNs. Strikingly, lung migratory CD103(+) DCs were not productively infected by influenza virus and thus were able to induce virus-specific CD8(+) T cells through the cross-presentation of antigens from virally infected cells. We also observed that CD103(+) DC resistance to infection correlates with an increased anti-viral state in these cells that is dependent on the expression of type I IFN receptor. These results show that efficient cross-priming by migratory lung DCs is coupled to the acquisition of an anti-viral status, which is dependent on the type I IFN signaling pathway.